Genome wide association studies reveals genetic loci associated with water logging tolerance in Soybean [Glycine max (L.) Merr.]: Genome wide association studies reveals genetic loci associated with water logging tolerance in Soybean [Glycine max (L.) Merr.] - SUBHASH CHANDRA; M B RATNAPARKHE; G K SATPUTE; SANJAY GUPTA; GIRIRAJ KUMAWAT; K RUCHA; DIPENDRA SINGH; V. NATARAJ; R RAGHUVANSHI; A CHITIKININI; RAJEEV VARSHNEY; AJAY K SINGH; et al. (Journal of Oilseeds Research, 2023)
In this investigation, a GWAS analysis was performed for four water logging tolerance traits in a panel of 265 soybean germplasm accessions with 66719 SNPs. A total of 29 SNPs and some candidate genes associated with different water logging tolerance traits were identified. This study also identified some soybean accessions, having superior water logging tolerance ability at vegetative and reproductive stages, which may be used as potential donors in soybean improvement programs.